Navigating Vocabulary in Rural Classroom: A Comparative Case Study of Indonesia and Malaysia - Zahrani Esa Muliya (Fakultas Ilmu Budaya, Universitas Brawijaya, 2026)
Several schools in rural areas receive less attention from the government. At times, English learning in rural schools is different from the urban schools due to several factors. This study explored teachers’ beliefs, strategies, and challenges in teaching vocabulary to elementary schools in rural areas. Participants of this study were one Elementary English teacher at Riau, Indonesia and one Elementary English teacher at CLC Sabah, Malaysia. The data were collected by using semi-structured interviews conducted online. This study revealed that vocabulary learning should be started in elementary school because it is the basis for students to learn other language skills. Furthermore, the strategies used by teachers in teaching vocabulary to elementary school students are using flashcards, songs, real objects, or memorization techniques. Moreover, the challenges encountered by teachers when teaching vocabulary in rural classrooms are students lack English knowledge, lack of motivation and support from their parents, and lack of school facilities. This study is expected to be used as a reflection for the government in the education sector to pay more attention to the schools in rural areas.